An Error Analysis in Writing Descriptive Text of Tenth Grades Students at SMK Antartika 1 Sidoarjo - Thalia Hafitsa Mulya; Dian Novita (Proceedings of The ICECRS, 2021)
The aimed of this study to identify the error in writing descriptive text made by the tenth grade students of SMK Antartika 1 Sidoarjo. The researcher utilizes quantitative research method. The population of this study is the tenth grade students of SMK Antartika 1 Sidoarjo. The researcher uses total sampling as the sampling technique. The researcher takes 34 students of X TPM 2. The data instrument of this study is students’ test result. In this study, the researcher used 3 types of analyzed data based on Miles and Huberman theory. The researcher analyzed the errors made by the students use the theory of Corder (1973). The result showed that The tenth graders’ of SMK 1 Antartika Sidoarjo still made error in writing descriptive text in four kinds of error based on Corder (1973) theory, which are omission, addition, selection, and ordering. The students made error in omission 67 times or 30% of total error, 21 times or 10% made error in addition, 103 times or 47% made error in selection, and 30 times or 13% made error in ordering. The most error the students made is selection error. It means that the students still do not know how to use correct word that is appropriated with the context. The student still translate Indonesia into English directly without considering the context.